"SECURITIES" – BASIC PRINCIPLES OF LEGISLATIVE REGULATION, ISSUES FOR DEVELOPMENT - Tedoradze, Irakli (European Scientific Journal, ESJ, 2015)
Securities law exists because of unique informational needs of investors. Securities are not inherently valuable; their worth comes only from the claims they entitle their owner to make upon the assets and earnings of the issuer or the voting power that accompanies such claims. The value of securities depends on the issuer’s financial condition, products and markets, management, and the competitive and regulatory climate. Securities laws and regulations aim at ensuring that investors receive accurate and necessary information regarding the type and value of the interest under consideration for purchase.